High-Resolution Computed Tomography of the Pulmonary Manifestations of Connective Tissue Diseases - Jacob, J.; Nair, A.; Hansell, David M. (Seminars in Respiratory and Critical Care Medicine, 2014)
Pulmonary disease is common in patients with connective tissue disease (CTD) and confers significant morbidity and mortality. High-resolution computed tomography (HRCT) provides considerable information regarding the distribution and severity of thoracic disease in CTD. Different anatomical compartments of the lung can be simultaneously affected in a given individual. Furthermore, lung injury may not be solely related to the underlying CTD, but may be caused by treatment or infections. Finally, the risk of developing cancer is increased in patients with certain CTDs. In this review, the HRCT manifestations of CTD are initially discussed with respect to the different compartments involved, followed by a description of the spectrum of pulmonary disease commonly occurring in specific CTDs.
Keywords: computed tomography; imaging; connective tissue diseases